The Need for Using Traditional and Modern Teaching Methodologies in the Conditions of the COVID-19 Pandemic - Parlić Božović, Jasna; Cenić, Dragan (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
There is no ideal class, but there are many ways to make teaching more interesting and better, putting an emphasis on the student as the main subject in the teaching process. No form of teaching work is perfect, it is very important not to keep the same principle of work and combine teaching and working methods according to the teaching unit (lesson) and class. Electronic social networks support independent learning management, learning through interactive communication, cooperation, knowledge creation and creation of a learning chain of interested and active actors. The Internet relocates the learning process from schools to cafes and other private environments, according to the principle of mobile classrooms. However, at present time of distance learning, due to the COVID-19 pandemic current situation, the student is allowed to be able to plan both the time and place for learning, following its own interests and using the electronic media. In that way, students easily and quickly become more independent for self-education process and preparation for lifelong learning, which becomes a lifestyle in new technological conditions. New information society challenges many dimensions of the traditional functioning of the education system. What is indisputable is the role and importance of education, both for the survival and development of society and individuals. Modern technologies have radically changed the physiognomy of modern society, needs and the way of meeting needs, and standards in all levels of social life. There is a constant need for a new education policy and strategy. New technologies create new work organization, the need for new occupations and educational backgrounds. Many problems in the society arise precisely in the field of education. The problem of educational efficiency, unclear competencies acquired through simple reproductionof existing educational profiles, without new educational competencies for the completely new occupations, the traditional way of education, with reproduction of learned, without clear vision of usefulness and usability of knowledge, are just some of the manifest forms of crisis society-education. The application of new educational technology is a requirement of the new education strategy, from which is being expected to increase the efficiency of educational and learning process. A society that is unprepared to implement modern technological achievements is doomed to stagnation, as well as to numerous conflicts and marginalization. On the other hand, investing in education, modernizing the premises in education, content and educational technology, has a reciprocal impact on the development of society. In the conditions of the COVID-19 pandemic, the information age proved to be appropriate and much needed by proving to be adequate to change traditional notions about matter, space, time, energy, and even about education. In these conditions, the role of teachers, schools, education, the nature of learning, and the methodology of teaching has changed. The new living conditions imposed by the COVID-19 pandemic have fundamentally changed the way teaching, business, entertainment, war technology, and educational technology. Educational technology consists of knowledge and achievements in various scientific fields: pedagogy, didactics, methodology, psychology, cybernetics, communication, etc. In these conditions, teaching methodology must rely on modern educational technology, on a systematic and organized process of applying modern techniques and technology in improving the quality of the teaching process in the field of efficiency, optimality, applicability and acquisition of knowledge. Knowledge, use and application of modern information technologies, in these conditions, is the content of modern literacy and cultural pattern. All of these are challenges for the methodology in teaching social sciences and humanities. The methodology of teaching social sciences and humanities is, more than the methodology of any other science field, facing important challenges. All the changes caused by the COVID-19 pandemic in society and life, through the teaching social sciences and humanities, should be approximated, explained, and interpreted in a way that will not distance these sciences from high school students, who will not create a repulsive attitude, "bogy" incomprehensible reading, as boring classes to be avoided. Precisely through the use of the possibilities of modern technologies, the teaching work should be refreshed, innovated and activated, so that the knowledge is updated both in the content and in the teaching-methodological sense. Finally, our hypothesis set at the beginning of this theoretical study is confirmed, modern forms of work and innovative approaches in the educational process are the future of the educational process. Expert authors agree that there are no good results without the application of educational technology, new methods and forms of work in the teaching process. Developed societies have long used this method and we can say that this is one of the reasons for their development and progress. However, appreciating all the above, the recommendation and conclusion of this paper is that with the use of new benefits and advantages in teaching, as well as the current need for distance learning, which is only feasible due to the COVID-19 pandemic, do not forget to use traditional teaching style as reliable support for performing and adequately placing educational tasks today and in the future. Spoken word is in any case an irreplaceable variant to which we should return according to the social crisis caused by the mentioned problems.
Keywords: traditionalism; contemporary; teaching preparation; teaching; realization of what is planned in teaching; COVID-19 pandemic